Pemanfaatan Limbah Ampas Kopi Menjadi Sabun Batang Organik Guna Meningkatkan Ekonomi Masyarakat Desa - Fitri Noviyanti; Anggi Liyandinny Purba; Manda Wulandari; Jesika Melina Simamora; Richard Tambunan; Fandra Dikhi Januardani; Rosintan Sipayung (Jurnal Pengabdian Cita Masyarakat, 2025)
This community service project addresses the environmental degradation and economic stagnation in Batu Silangit Village caused by unmanaged spent coffee grounds. Historically, this waste contributes to methane emissions and soil toxicity. Therefore, this study implements a circular economy strategy by converting coffee residue into organic bar soap. The methodology utilizes Community Based Participatory Research (CBPR) combined with the "Melt and Pour" technology, ensuring safety for untrained participants. Results indicate that the produced soap meets dermatological standards with a pH range of 9.5 to 10.1 and possesses significant antibacterial and antioxidant properties. Economically, the initiative is highly viable, demonstrating a profit margin exceeding 50% due to zero-cost raw materials. In conclusion, this program successfully transforms ecological burdens into financial assets. It provides a sustainable model for rural empowerment by integrating environmental mitigation with micro-entrepreneurship, fostering a resilient village economy through the practical application of effective green technology and innovative waste-to-wealth principles.